1997
DOI: 10.1088/0953-8984/9/40/011
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ti addition on the soft magnetic properties of Fe - N films

Abstract: FeTiN films with good soft magnetic properties were prepared on Si and NaCl single-crystal substrates by facing-targets sputtering (FTS). The effects of Ti addition on the structural and magnetic properties of Fe - N films were investigated. Ti has been found effective in improving the soft magnetic properties as well as the thermal stability of FeN films. For the films containing 5 - 12 at.% Ti prepared under sputtering conditions of = 0.04 - 0.07 Pa, a substrate temperature of , and a sputtering rate of , t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 16 publications
1
16
0
Order By: Relevance
“…Part A presents room temperature FMR results that show a clear signature of a deposition field induced uniaxial anisotropy. The uniaxial field parameter increases with N x for nitrogen levels above about 4 at. %.…”
Section: Competition Between Cubic and Uniaxial Anisotropymentioning
confidence: 91%
See 2 more Smart Citations
“…Part A presents room temperature FMR results that show a clear signature of a deposition field induced uniaxial anisotropy. The uniaxial field parameter increases with N x for nitrogen levels above about 4 at. %.…”
Section: Competition Between Cubic and Uniaxial Anisotropymentioning
confidence: 91%
“…It has been found that the addition of small amounts of a third element Q to form ternary Fe-Q-N phases, typically Hf, Ta, Ti, or Zr, can serve to increase thermal stability. 4,16,17 For pure iron, additions of such a Q element at levels up to about 5 at. % have been found to dissolve substitutionally into the bcc lattice with no substantial effect on the structure or magnetic properties.…”
Section: Overview Of the Fe-n And Fe-q-n Film Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…In attempts to make interstitial Fe-N more stable, addition or doping of impurity element(s) was proposed in such a way * mgupta@csr.res.in/dr.mukul.gupta@gmail.com that the amount of impurity must be low enough to affect the structural or the magnetic properties adversely [9,[21][22][23][24][25][26][27][28][29][30][31][32][33][34]. Such impurity doped systems were termed as Fe-X-N with X = few at.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that certain nitrogen-containing nanocrystalline films composed of iron with 1-10 at% of a transition element, like Ta, Ti, Cr, Zr [1][2][3][4] have good soft magnetic properties. For thin films (o200 nm), where eddy current losses are small, magnetic losses at high frequencies are mainly determined by the presence of ferromagnetic resonance (FMR) with a frequency f FMR Egð4pM s H K Þ 1=2 : Here, g is the gyromagnetic ratio (0.446 MHz/Oe), M s the saturation magnetization and H K the effective anisotropy field in the plane.…”
mentioning
confidence: 99%